The Synergistic Effect of Zingiber officinale Roots and Vitamin E on some Reproductivity and Physiological Traits in Rations of Kids Iraqi Black Goat: Mudhaffar N. AL-Saigh ,Latif E. Hadi - AL-Saigh, Mudhaffar N. (The Iraqi Journal of Veterinary Medicine, 2010)
The aim of this study was to investigate the effect of using milled ZingiberRhizome and vitamin E on some reproductivity traits (serum hormones levels, SSH andtestosterone and semen characters).Eighteen Iraqi Black kids at age of 5-6 months were bought and divided intothree groups equally (body weight was considered), each group contained 6 kids. Thisstudy was carried out in Animal’s Farm, College of Veterinary Medicine, University ofBaghdad from 1st November 2007 up to end of May 2008, and treated as followed:The first group (Z) (Zingiber group) was fed on concentrates diet (400 g/head)daily which contained 10 g of zingiber (2.5% of diet). The second group (Z+E)(Zingiber group + vit. E) was given the same concentrate diet mentioned above (400g/head) daily and administered of vit. E with a dose of 400 mg/head orally givenbimonthly for each animal. Animals of the third group were fed on a concentrate diet(400 g/head) daily which was free of Zingiber kept as a control group.The results revealed the followings:With experimental period progress, SSH hormone level of all groups wereincreased, while no significant differences among different groups were obtained inspite of mathematically increased in group 1 and 2 compared with the control group.Testosterone hormone level was progressively increased in all groups, the first andsecond groups showed significantly (P<0.05) increased compared with the controlgroup at end of the experimental period.The kids in the second and first groups showed their pubertal stage at earlier agethan the control group. While the second group showed more earlier than the firstgroup.Most semen quality characters recorded mathematically or significantly(P<0.05) better in the group 1 and 2 compared with the control group. While theanimals in the 2nd group gave better values in most semen characters compared withthose in the first group.It is concluded that by using Zingiber rhizomes caused an improvement of somereproductivity and physiologically traits of male goat kids by administration of Vit. Ecaused more improving.